Local Expansion of Donation After Circulatory Death Kidney Transplant Activity Improves Waitlisted Outcomes and Addresses Inequities of Access to Transplantation. Issue 2 (26th August 2016) - Mirshekar‐Syahkal, B.; Summers, D.; Bradbury, L. L.; Aly, M.; Bardsley, V.; Berry, M.; Norris, J. M.; Torpey, N.; Clatworthy, M. R.; Bradley, J. A.; Pettigrew, G. J.
Abstract : In the United Kingdom, donation after circulatory death (DCD) kidney transplant activity has increased rapidly, but marked regional variation persists. We report how increased DCD kidney transplant activity influenced waitlisted outcomes for a single center. Between 2002–2003 and 2011–2012, 430 (54%) DCD and 361 (46%) donation after brain death (DBD) kidney‐only transplants were performed at the Cambridge Transplant Centre, with a higher proportion of DCD donors fulfilling expanded criteria status (41% DCD vs. 32% DBD; p = 0.01). Compared with U.K. outcomes, for which the proportion of DCD:DBD kidney transplants performed is lower (25%; p < 0.0001), listed patients at our center waited less time for transplantation (645 vs. 1045 days; p < 0.0001), and our center had higher transplantation rates and lower numbers of waiting list deaths. This was most apparent for older patients (aged >65 years; waiting time 730 vs. 1357 days nationally; p < 0.001), who received predominantly DCD kidneys from older donors (mean donor age 64 years), whereas younger recipients received equal proportions of living donor, DBD and DCD kidney transplants. Death‐censored kidney graft survival was nevertheless comparable for younger and older recipients, although transplantation conferred a survival benefit from listing for only younger recipients. Local expansion in DCD kidney transplant activity improves survival outcomes for younger patients and addresses inequity of access to transplantation for older recipients. Abstract : The authors report the impact on a single center's kidney waitlist population following local expansion in circulatory death donation, show a survival advantage for young listed patients, and address inequity of access to transplantation for elderly recipients.